Catalytic Methods for the Synthesis of Carbon Nanodots and Their Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The current endeavor of publishing a reprint on the astounding field of research on carbon dots has its roots in the launch of the Special Issue entitled "Catalytic methods for the synthesis of carbon nanodots and their applications”. Ever since this Special Issue was launched on 29th August 2022, it has attracted great attention from researchers worldwide. Grateful thanks are due to Dr. Nimala Kumar Jangid and coworkers from India; Dr. Syed Hadi Hasan and coworkers from India; Dr. Lerato L Mokoloko and coworkers from South Africa; Dr. Siti Kastom Kamarudin and coworkers from Malaysia; Dr. Selvaraj Roomani and coworkers from India; Dr. Ahmad Umar and coworkers from India, Saudi Arabia and USA; Dr. Ramon Moreno-Tost and coworkers from Spain; Dr. Jae Hong Kim and coworkers from South Korea and Japan; Dr. Yong RokLee and coworkers from India, South Korea and UAE; and Dr. Joydeep Das from India for their scientific contributions. In a duration of 14 months, 12 state-of-the-art papers were published. Out of the 12 papers published, 4 were comprehensive reviews and 8 were original research articles. This shows the enthusiasm that this research topic has aroused globally.